Aerobic VS Anaerobic Exercise on Body Composition and Hormonal Adaptations in Athletes and Non-Athletes: A Randomized Controlled Trial - Md Shahariar Kabir; Sunita Yadav; Subhashis Biswas; Sangeeta Pradhan; Vlad Adrian Geantă (Journal of Coaching and Sports Science, 2025)
Background:This study examined the differential effects of aerobic and anaerobicexercise on body composition and hormonal adaptations in athletes and non-athletes, providing evidence-based recommendations for optimizing fitness andhealth outcomes, such as training duration, frequency, and the combination ofaerobic and anaerobic exercises.Aim: These specific recommendations aim to enhanceboth physical performance and overall health, tailored to the needs of differentpopulations.Methods: A randomized controlled trialinvolving 120 males(60 athletes,60 non-athletes, aged 18–25 years) was conducted. Participants engaged in 12 weeks ofeither aerobic or anaerobic exercise. The aerobic group performed moderate-intensity continuous training (MICT) for 50 minutes persession, 3 times per week,while the anaerobic group performed 30 minutes of resistancetraining followed by 20 minutes of high-intensity interval training (HIIT) 3 times per week. Dual-energy X-ray absorptiometry (DXA) measured body composition, while blood samplesassessed testosterone, cortisol, and growth hormone levels. Mixed ANOVA analyzedthe effects of exercise type, athletic status, and time.Results: Anaerobic exercise led to significant increases in lean body mass andstrength, while aerobic exercise induced greater fat loss. Athletes exhibited morepronounced increases in testosterone and growth hormone levels, compared tonon-athletes.Conclusions:Tailoredexerciseprograms,consideringfitnesslevelsandgoals,canoptimize body composition and hormonal health. These findings have practicalimplications for designing effective training regimens for diverse populations.